Non‐canonical phosphoglycerate dehydrogenase activity promotes liver cancer growth via mitochondrial translation and respiratory metabolism - Shu, Ying; Hao, Yijie; Feng, Junru; Liu, Haiying; Li, Shi‐ting; Feng, Jiaqian; Jiang, Zetan; Ye, Ling; Zhou, Yingli; Sun, Yuchen; Zhou, Zilong; Wei, Haoran; et al. (The EMBO journal, 2022)
Phosphoglycerate dehydrogenase (PHGDH) is a key serine biosynthesis enzyme whose aberrant expression promotes various types of tumors. Recently, PHGDH has been found to have some non‐canonical functions beyond serine biosynthesis, but its specific mechanisms in tumorigenesis remain unclear. Here, we show that PHGDH localizes to the inner mitochondrial membrane and promotes the translation of mitochondrial DNA (mtDNA)‐encoded proteins in liver cancer cells. Mechanistically, we demonstrate that mitochondrial PHGDH directly interacts with adenine nucleotide translocase 2 (ANT2) and then recruits mitochondrial elongation factor G2 (mtEFG2) to promote mitochondrial ribosome recycling efficiency, thereby promoting mtDNA‐encoded protein expression and subsequent mitochondrial respiration. Moreover, we show that treatment with a mitochondrial translation inhibitor or depletion of mtEFG2 diminishes PHGDH‐mediated tumor growth. Collectively, our findings uncover a previously unappreciated function of PHGDH in tumorigenesis acting via promotion of mitochondrial translation and bioenergetics. Synopsis This study reports a non‐catalytic tumorigenic role for serine biosynthesis enzyme phosphoglycerate dehydrogenase (PHGDH) in enhancing mitochondrial translation and respiratory metabolism in cancer cells, suggesting a new target for tumour progression. PHGDH localizes to the inner mitochondrial membrane in human liver cancer cells and patient tissues. PHGDH promotes translation of mtDNA‐encoded ETC proteins in catalytic activity‐independent manner. PHGDH forms a complex with mitochondrial translation factors ANT2 and mtEFG2, enhancing mtRRF interaction and mitoribosome recycling. PHGDH increases tumour growth in mice translation‐dependently by elevating respiratory metabolism. Graphical Abstract A novel non‐catalytic function of serine biosynthesis enzyme PHGDH spurs cancer cell protein translation for enhanced bioenergetics.